Pengaruh Gaya Pembelajaran SAVI terhadap Hasil Evaluasi Belajar Bahasa Inggris Kelas V Sekolah Dasar - Ina Magdalena; Adinda Ayuning D.P; Atina Triska Wahdini; Danty Amalya Rizky; Novfa Rizka Zahra (RC-INSTITUT, 2020)
This study aims to determine how the influence of the SAVI (Somatic, Auditory, Visual, Intellectual) model on the learning outcomes of English class VA and VB in SDN Karang Sari I. This research is a quasi-experimental study with a quantitative approach, while the sample used in this study is VA class students and VB, each of which numbered 20 people, the method of collecting data on learning outcomes using multiple-choice tests and observations. Data analysis techniques used in this study were the normality test, two variance homogeneity tests, and the hypothesis test (t-test) used to determine the effect of the SAVI (Somatic, Auditory, Visual, Intellectual) learning model on English learning outcomes of VA and VB students in SDN Karang Sari I. Based on statistical perceptions the comparison of t arithmetic with t table shows 0.000> 0.05, which indicates that there is a significant comparison between the learning outcomes of English students in grade VA and VB in SDN Karang Sari I.